Enhanced visible-light-driven photodegradation of Rh-6G by surface engineered Pd-V2O5 heterostructure nanorods. Issue 4 (August 2018) - Jayaraj, Santhosh Kumar; Paramasivam, Thangadurai
Graphical abstract: Highlights: Pd decorated on V2 O5 nanorods were prepared by hydrothermal method at 120 °C. Enhanced photodegradation (98%) was due to synergistic effect of Pd and V2 O5 . High surface area, light harvesting, lifetime and Pd content give good activity. Superoxide radicals (O2 − ) is major reactive species of photodegradation. They show good photostability and structural stability after continuous use. Abstract: Developing new photocatalysts for photodegradation of organic pollutants from the industries has become an important solution to water pollution. This work presents the improved photocatalytic performance of the surface engineered photocatalyst, Pd nanoparticles (NPs) decorated V2 O5 heterostructure nanorods (Pd-V2 O5 ), prepared by hydrothermal method. The Pd-V2 O5 heterostructures contain orthorhombic structured V2 O5 nanorods with their surface decorated with cubic structured Pd NPs. Small size of the Pd NPs (3.5 nm) has influenced and enhanced the visible light absorption through surface plasmon resonance. The number density of the Pd NPs on V2 O5 surface was controlled by varying the Pd precursor concentration as 1, 3, 5, 8 and 10 wt% PdCl2 during synthesis, and the pure V2 O5 was used as a control. Photocatalytic activity of Pd-V2 O5 on Rhodamine-6 G (Rh-6 G) dye was investigated under visible light irradiation. Degradation performance of Pd-V2 O5 has been significantly enhanced over pure V2 O5, with 5%Pd-V2 O5 showing the best degradation (98%) in 120 min. The highest degradation by 5%Pd-V2 O5 is due to the largest BET surface area (19 m 2 /g), highest reaction rate constant (1.8544 h -1 ), improved visible light harvesting, highest charge career lifetime (35.64 ns) and optimum Pd content. The 5%Pd-V2 O5 worked well with the pH environment of 7. The photocatalyst was found stable up to 3 cycles of photocatalytic experiment. The superoxide radicals (O2 − ) and electrons (e-) are the most favorable species involved in the photocatalytic degradation. These photocatalysts are thus engineered to attain the highest photodegradation efficiency with thorough understanding of the mechanism for the remarkable enhancement.